Batterer Intervention Systems : Issues, Outcomes and Recommendations. - Gondolf, Dr. Edward W. (Sage series on violence against women., 2001)
One of the most burning debates in the domestic violence field is over the effectiveness of batterer programs and how to improve them. Batterer Intervention Systems responds to this debate with research from a multi-site evaluation of batterer programs-the most comprehensive and extensive evaluation to date. It critiques current experimental evaluations, exposes the complex issues of evaluation, and presents alternatives to assessing effectiveness. A four-year follow-up of program participants reveals a surprising de-escalation of abuse, a subgroup of unresponsive repeat reassaulters, and the.